STUDY OF BATIK BASUREK IN THE CITY BENGKULU PROVINCE BENGKULU - Purnamawati, Sischa; Adriani, Adriani; Novrita, Sri Zulfia (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
Besurek Batik is a unique handicrafts Bengkulu motive distinctively Arabic calligraphy. This study to look at the shape of the motive and meaning of philosophy on motive. Method used is descriptive method qualitative . Collecting data using observation, interviews and documentation in the city of Bengkulu province of Bengkulu. Data type form of writing and non- writing (recording) the interviews, documentation and literature study. Data reviewed and analyzed by step data reduction, data presentation and conclusion. Extension of the validity of the data with observations, increase persistence and triangulation. The results showed that Batik Basurek consists of 12 motifs and ornaments sourced from naturalists shaped, other shapes and combinations. Kaligrafi motive of symbolizes religious. Burung Kuau motive symbolizes the God Is the God Esa. Motive relung paku symbolizes the wheel of human life. Motive jasmine flowers describe the symbolizes of beauty, elegance and prayer. Motive rafflesia flowers the symbolizes of gratitude. Motive kaganga is symbolizes the by writing script rejang derived from the area rejang lebong. Motive remis is shell small symbolizes of natural wealth rejang lebong. Motive durian symbolizes of patience. Floral teratai symbolizes the environment. Butterfly motif symbolizes of perfection. Â Keyword: Batik Basurek, the form of batik motifs, philosophy of batik motifs